Analisis Keterampilan Berpikir Kritis dan Kreatif Siswa SMK Kelas XI dalam Pembelajaran Matematika Berbasis PBL - Sulistyani, Niluh; Rustyningsih, Nadia (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
This research aims to analyze critical thinking and creative thinking skills in class XI mechanical engineering students at Leonardo Klaten Vocational School for the 2022/2023 academic year in mathematics learning using the Problem Based learning model. The subjects in this research were 30 students of class XI Mechanical Engineering B SMK Leonardo Pangudi Luhur Klaten academic year 2022/2023. The research was carried out in February 2023 – March 2023. Data collection techniques used were observation, tests and interviews. The results of observations and tests were analyzed using descriptive statistics assisted by Microsoft Excel to determine average scores and categories. The instruments used in this research include observation sheets, test questions and interview guides. The research results showed that the Problem Based Learning model implemented by the researcher was carried out at each meeting with a percentage of 79.54% in the good category at the first meeting and 81.81% in the very good category at the second meeting. Students' critical thinking skills in PBL-based learning reach the moderately critical category, while creative thinking skills fall into the moderately creative category judging from the average score and the majority of students' categories.